Positive airway pressure adherence and subthreshold adherence in posttraumatic stress disorder patients with comorbid sleep apnea - Krakow BJ; Obando JJ; Ulibarri VA; McIver ND (Patient Preference and Adherence, 2017)
Barry J Krakow,1–3 Jessica J Obando,2 Victor A Ulibarri,1,2 Natalia D McIver1,2 1Sleep & Human Health Institute, 2Maimonides Sleep Arts & Sciences, Albuquerque, 3Los Alamos Medical Center, Los Alamos, NM, USA Study objectives: Patients with comorbid posttraumatic stress disorder (PTSD) and obstructive sleep apnea (OSA) manifest low adherence to continuous positive airway pressure (CPAP) due to fixed, pressure-induced expiratory pressure intolerance (EPI), a subjective symptom and objective sign aggravated by anxiety sensitivity and somatosensory amplification. As advanced PAP therapy modes (ie, auto-bilevel PAP [ABPAP] or adaptive servo-ventilation [ASV]) may address these side effects, we hypothesized such treatment would be associated with decreased expiratory intolerance and increased adherence in posttraumatic stress patients with co-occurring OSA.Methods: We reviewed charts of 147 consecutive adult patients with moderately severe posttraumatic stress symptoms and objectively diagnosed OSA. All patients failed or rejected CPAP and were manually titrated on auto-adjusting, dual-pressure ABPAP or ASV modes in the sleep laboratory, a technique to eliminate flow limitation breathing events while resolving EPI. Patients were then prescribed either mode of therapy. Follow-up encounters assessed patient use, and objective data downloads (ODDs) measured adherence.Results: Of 147 charts reviewed, 130 patients were deemed current PAP users, and 102 provided ODDs: 64 used ASV and 38 used ABPAP. ODDs yielded three groups: 59 adherent per insurance conventions, 19 subthreshold compliant partial users, and 24 noncompliant. Compliance based on available downloads was 58%, notably higher than recently reported rates in PTSD patients with OSA. Among the 19 partial users, 17 patients were minutes of PAP use or small percentages of nights removed from meeting insurance compliance criteria for PAP devices.Conclusion: Research is warranted on advanced PAP modes in managing CPAP failure in PTSD patients with comorbid OSA. Subthreshold adherence constructs may inform clinical care in a patient-centric model distinct from insurance conventions. Speculatively, clinical application of this transitional zone (“subthreshold” number of hours) may increase PAP use and eventual adherence. Keywords: obstructive sleep apnea, upper airway resistance syndrome, CPAP, compliance, auto-bilevel, adaptive servo-ventilation